2018
DOI: 10.1073/pnas.1805442115
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations indicate the functional loop-to-coiled-coil transition in influenza hemagglutinin is not downhill

Abstract: Influenza hemagglutinin (HA) mediates viral entry into host cells through a large-scale conformational rearrangement at low pH that leads to fusion of the viral and endosomal membranes. Crystallographic and biochemical data suggest that a loop-to-coiled-coil transition of the B-loop region of HA is important for driving this structural rearrangement. However, the microscopic picture for this proposed "spring-loaded" movement is missing. In this study, we focus on understanding the transition of the B loop and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 78 publications
(80 reference statements)
2
22
0
Order By: Relevance
“…to the extended helical intermediate is largely driven by trimerization of the A-helix and not the Bloop's loop-to-helix transition [103] Interestingly, in the soluble BHA ectodomain that lacks the transmembrane anchor, a direct, two-state transition from the pre-to post-fusion state was observed by HDX-MS. This striking result underscored the fact that in order to understand the mechanism of viral protein-mediated membrane fusion, it is necessary to examine how the conformational changes are carried out in the context of the complete viral system.…”
Section: Direct Monitoring Of the Transitions Between Conformational mentioning
confidence: 97%
See 2 more Smart Citations
“…to the extended helical intermediate is largely driven by trimerization of the A-helix and not the Bloop's loop-to-helix transition [103] Interestingly, in the soluble BHA ectodomain that lacks the transmembrane anchor, a direct, two-state transition from the pre-to post-fusion state was observed by HDX-MS. This striking result underscored the fact that in order to understand the mechanism of viral protein-mediated membrane fusion, it is necessary to examine how the conformational changes are carried out in the context of the complete viral system.…”
Section: Direct Monitoring Of the Transitions Between Conformational mentioning
confidence: 97%
“…Consistent with this, computational studies also suggest that both the HA2 A-helix and B-loop segments can sample diverse structural states as they transition to the extended helical intermediate. Moreover, the computational modeling suggested that the transition to the extended helical intermediate is largely driven by trimerization of the A-helix and not the B-loop's loop-to-helix transition [103].…”
Section: Direct Monitoring Of the Transitions Between Conformational mentioning
confidence: 99%
See 1 more Smart Citation
“…Various mechanisms have been proposed for HA-mediated membrane fusion, based on equilibrium prefusion and postfusion crystal structures and biochemical evidence, but the details of this highly dynamic process are largely unknown. In PNAS, Lin et al (13) present important new insight into the energetic landscape and the dynamics of the pH-induced conformational changes that underlie HA-mediated membrane fusion based on all-atom molecular dynamics simulations of the full B-loop trimeric structure of HA 2 .…”
Section: Hemagglutinin As An Archetypementioning
confidence: 99%
“…While the mechanism of HA refolding has been difficult to characterize experimentally, molecular dynamics simulations offer a tractable approach to the problem. Lin et al (13) report all-atom, explicit-solvent molecular dynamics simulations to characterize the refolding of the trimeric B loop of the group 2 H3 HA. In the spring-loaded model, the B loop functions as a pH-dependent structural trigger that initiates and guides the initial HA refolding process.…”
Section: Molecular Dynamics Simulations Of Ha Refoldingmentioning
confidence: 99%